Estudo de mecanismos de segurança para proteção do roteamento em redes de sensores sem fio - Sergio de Oliveira (2008)
Wireless Sensor Networks (WSN) are more subject to enemy action than conventional networks due to their hardware and energy constraints and due to hostile environment in which they can be inserted. This scenario is too favorable to denial of service attacks, especially in routing function, one critical function in any network. This work is focused in routing protecting in WSN. It presents a study on WSN security focusing on routing and proposes an architecture management to extend the network lifetime by setting up the several security solutions and two mechanisms for security. The first mechanism is a key establishment protocol proposed to neighboring nodes use cryptographic algorithms to ensure the link layer access control, inhibiting intruder nodes presence in network. The second mechanism is a routing algorithm with alternative routes to increase network resilience against intruders' presence and, moreover, enable intruder detection of nodes running denial of service attacks on routing. The architecture of security management presented enables that security mechanisms are used only when necessary, thus avoiding unnecessary energy consumption when there is no intruders' presence. This work evaluates the computational cost, energy consumption, efficiency and scalability of the solutions presented, indicating their viability for WSN. The impact of the attacks and the effectiveness of the proposed mechanisms to protect the network against attacks are also analyzed. The results show the work has scalability, is efficient and the additional energy consumption don't decrease significantly the network time life.